2015
DOI: 10.1039/c5ta07554h
|View full text |Cite
|
Sign up to set email alerts
|

Highly pseudocapacitive Nb-doped TiO2 high power anodes for lithium-ion batteries

Abstract: Nb-doped and pure TiO2 (anatase) nanoparticles were synthesized via a continuous hydrothermal flow synthesis reactor and investigated as electrode material for lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 46 publications
(81 reference statements)
3
71
0
Order By: Relevance
“…More importantly, the diffraction peaks of the Nb‐doped samples at 2 θ ≈27.4° slightly shifted to a lower 2 θ value (enlarged insets in Figure a and b). This can be ascribed to the lattice expansion, resulting from the substitution by the larger Nb 5+ ions (radius=0.64 Å) for the smaller Ti 4+ ions (0.61 Å) in the rutile structure . Furthermore, the intensities of the peaks increased with reaction time (inset in Figure a), indicating that the crystallinity of rutile TiO 2 increased.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…More importantly, the diffraction peaks of the Nb‐doped samples at 2 θ ≈27.4° slightly shifted to a lower 2 θ value (enlarged insets in Figure a and b). This can be ascribed to the lattice expansion, resulting from the substitution by the larger Nb 5+ ions (radius=0.64 Å) for the smaller Ti 4+ ions (0.61 Å) in the rutile structure . Furthermore, the intensities of the peaks increased with reaction time (inset in Figure a), indicating that the crystallinity of rutile TiO 2 increased.…”
Section: Resultsmentioning
confidence: 94%
“…Atom doping, such as with Nb 5+ ions, provides another effective strategy to enhance the electronic conductivity and lithium‐ion diffusion. It was reported that the Nb‐doping in TiO 2 can improve the capacity, resulting from the contribution of the surface storage . For example, a Nb‐doped rutile TiO 2 (Ti 0.94 Nb 0.06 O 2 ) electrode material reported by Usui et al.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, TCM exhibits better pseudocapacitive behaviors than CM and TNP. Moreover, in order to further investigate the difference of pseudocapacitive behavior among TCM, CM, and TNP in detail, the b ‐values of TNP, CM, and TCM electrodes are determined and compared at various battery potentials in Figure j . It is evident that the contribution of pseudocapacitive storage in TCM is greater than that of TNP and CM across the entire potential range.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, the extreme large surface area to volume ratio enabled ultrasmall nanoparticles enhance their pseudocapacitive behavior that promotes reversible electrochemical reaction on or near particle surface. [36b,38] Therefore, by introducing ultrasmall tin nanoparticles in 3D interconnected porous carbonaceous structure, pseudocapacitive contribution can be greatly enhanced, generating the high‐rate capability and outstanding cycle stability of TCM.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore this work used nanopowders of ITO (with 10 at% Sn) that were directly synthesised as nanoparticles dispersed in a liquid media, using a continuous hydrothermal flow synthesis (CHFS) method, as discussed in previous work [4,18,19]. The effect of the addition of different dispersants on the level of agglomeration of the nanopowders along with a comparative study of conventional and microwave heating techniques on the characteristics of the films was investigated.…”
Section: Introductionmentioning
confidence: 99%